AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PEPAYA (Carica papaya L.) TERHADAP Staphylococcus aureus - Sarkono, Sarkono (Samota Journal of Biological Sciences, 2022)
Staphylococcus aureus is one of the pathogenic bacteria that causes pyogenic infections that lead into several diseases such as ulcers, acne, throat infections, food poisoning, and pneumonia. Papaya leaves (Carica papaya L.) contains flavonoid, tannins, alkaloids, and saponins that has functioned as an antibacterial. The aim of this research to test the effectiveness extracts of 96% ethanol, ethyl acetate, n-hexane, and infusion of aquadest of papaya leaves, as well as to see the effect of the concentration of the best extracts using the sumuran method. The results were carried out by measuring the diameter of the clear zone formed in each extract. Ethyl acetate extract of papaya leaves had the highest activity with a clear zone diameter 21.5 mm, followed by aquadest, n-hexane, and 96% ethanol infusion extract with each clear zone has diameter 15.8 mm, 13.0 mm, and 0.0 mm. The higher the concentration of the extract, the higher the inhibitory power, this can be seen from the results of the measurement of the clear zone of papaya leaf ethyl acetate extract with a concentration range of 80%, 60%, 40%, and 20%, respectively 21.5 mm, 13, 0mm, 8.5mm, and 0.0 mm. This shows that papaya leaves (Carica papaya L.) can be used as an antibacterial against Staphylococcus aureus.